A genome-wide association study of seed size, protein content, and oil content using a natural population of Sichuan and Chongqing soybean - He, Qingyuan; Xiang, Shihua; Yang, Huawei; Wang, Wubin; Shu, Yingjie; Li, Zhengpeng; Yang, Xiaoyan; Wang, Songhua (Euphytica, 2021)
Soybean seeds contain high levels of oil and protein, providing 57 and 69% of a person's dietary requirements, respectively. Although many quantitative trait loci for the 100-seed weight (100SW), protein content (PRC), and oil content (OIC) have been reported, their genetic controls in soybeans remain unclear. The QTL–allele constitution of three traits in the Sichuan and Chongqing eco-regions population (SCLBP) was studied using a representative sample composed of 228 accessions. These were tested in four environments and analyzed using 135 simple sequence repeats (SSR) and 107,081 valid single nucleotide polymorphism linkage (SNP) markers. The range of 100SW, PRC, and OIC in SCLBP accessions were 4.82–33.35, 36.47–49.75%, and 14.68–21.77%, respectively. The heritability ( h 2 ) and genetic coefficient of variation ( GCV ) of the three traits were high. As a result, 26, 33, and 31 QTLs were found using SSR for 100SW, PRC, and OIC, respectively. The allele of Sat_260 for 100SW was detected in the four environments. In addition, 28, 198, and 250 loci for 100SW, PRC, and OIC, respectively, were found using SNP and mixed linear model (MLM). Further SNP haplotype analysis revealed that 13, 35, and 60 blocks were found for 100SW, RPC, and OIC, respectively. The block of Gm11_9895764-9,917,646 for 100SW was simultaneously detected in the four environments. Among these QTLs, 1, 5, and 7 for 100SW, PRC and OIC were found using two methods of SSR and SNP at the same time. A majority of these QTLs overlapped with the previously reported loci. However, 9, 11, and 9 loci for 100SW, PRC, and OIC using SSR; and 3, 5, and 8 for 100SW, PRC, and OIC hadn’t been reported using SNP. Moreover, the genes of Glyma.11g130800, Glyma.13g217000, and Glyma.08g122600 were considered the most likely genes controlling 100SW, PRC, and OIC, respectively. These findings provide evidence for mixed major plus polygenes inheritance for the three traits and an extended understanding of their genetic architecture for the molecular dissection and breeding of soybeans.